A 10 × 10 Multi-Band MIMO Antenna System for LTE, 5G, Wi-Fi 7, and X-Band Communication Applications - Ming-An Chung; Kai-Xiang Chen; Chia-Chun Hsu; Chia-Wei Lin (IEEE Access, 2025)
To attend with the needs of modern wireless communication equipment, this paper proposes a multi-band planar antenna MIMO system. The antenna system operates in the frequency range of 0.8-1.04 GHz, 1.6-2.71 GHz, and 4.69-11.5 GHz, supporting LTE, 5G NR, Wi-Fi 7, and X bands. The antenna proposed in this paper is 60 mm $× 10$ mm. A feed-through coupling structure reduces its size and achieves broadband coverage to adapt to increasingly compact electronic communication. The design uses multi-branch microstrip lines and long slot structures to ensure high gain and high efficiency over a wide spectrum and achieve omnidirectional radiation of the antenna. In the proposed MIMO antenna system, the envelope correlation coefficient (ECC) remains below 0.5 and even approaches zero at high frequencies. Additionally, the system maintains overall isolation below -10 dB, demonstrating excellent signal isolation and anti-interference capabilities. In order to confirm the impact of antenna radiation on the human body, the analysis results of the specific absorption rate (SAR) and power density (PD) confirmed that the radiation impact of the antenna system on the human body is lower than the international standard value. The MIMO antenna system proposed in this paper is simple in design and doesn’t require additional passive components in the circuit, which greatly reduces the manufacturing cost. When integrated into laptops, routers, and smartphones, it exhibits stable antenna performance, making it efficient and flexible for application in a variety of wireless communication environments.